Solubility determination, model evaluation, Hansen solubility parameter and thermodynamic properties of benorilate in six pure solvents and two binary solvent mixtures. (February 2021) - Sha, Jiao; Ma, Teng; Huang, Zibo; Hu, Xiaoran; Zhang, Ruke; Cao, Zidan; Wan, Yameng; Sun, Renren; He, Haixia; Jiang, Gaoliang; Li, Yu; Li, Tao; et al.
Highlights: Solubility of benorilate in pure solvents and binary solvent mixtures was measured. Hansen solubility parameter was applied to analyze the solubility behavior. Six different models were used to correlate the solubility data. Thermodynamic properties of the solution were calculated by Van't Hoff equation. Abstract: The equilibrium solubility and thermodynamic properties of benorilate in six pure solvents (methyl acetate, n-propyl acetate, n-butyl acetate, n-pentyl acetate, DMAC and DMSO) and two binary solvents (DMAC + n-pentyl acetate, DMSO + n-pentyl acetate) were reported. Solubility determinations were performed through the laser monitoring method at T = (278.15–323.15) K and p  = 0.1 MPa, except DMSO at (293.15–323.15) K. The measurement results illustrated that the solubility of benorilate in all the six mono-solvents and two binary solvents shows a positive relation with temperature variation. And with the mass fraction of positive solvents (DMAC, DMSO) in the binary mixed solvents increasing, the solubility of benorilate also rises. And then, the Hansen solubility parameter (HSP) of benorilate as well as solvents selected were summarized to analyse the probabilities of miscibility between solute and solvents. The results indicate that the HSP could explain the solubility trend well, and the miscibility of benorilate with selected solvents is caused by a combination of factors. In addition, all recorded solubility of benorilate in pure solvents were regressed by λh, modified Apleblat, Two-Suffix Margules, NRTL and UNIQUAC models, while solubility of benorilate in two binary solvents were regressed by λh, modified Apleblat, Three-Suffix Margules, NRTL and UNIQUAC models. By calculating the deviation between the experimental data and the regression data, it shows that the modified Apelblat model and λh model can provide more accurate correlation results for the solubility of benorilate in all the solvents studied. Furthermore, the apparent thermodynamic properties of benorilate in all solvents were calculated and investigated by the Van't Hoff equation. The results demonstrate that the dissolution process of benorilate is an endothermic, non-spontaneous process driven by entropy.